Determinants of Behavioural Intention to Use Buy Now Pay Later (BNPL) Services among Gen Z in Batu Pahat - Lau, Wei Sheng; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2026)
Buy Now Pay Later (BNPL) services are growing rapidly and becoming a popular payment alternative to traditional credit cards and installment loans, especially among digitally savvy Gen Z for convenience and flexibility. However, financial literacy of users, data privacy issues, lack of clear regulatory framework, and the increasing of debt accumulation have concerned by people to more understanding in this. This study aims to investigate the relationship between determinants and behavioural intention to use Buy Now Pay Later (BNPL) services among Gen Z in Batu Pahat. Four determinants which are performance expectancy, effort expectancy, social influence, and perceived risk are analysed to understand their relationship on behavioural intention to use Buy Now Pay Later (BNPL) services. Using the UTAUT with additional perceived risk, and a quantitative approach was used. Data was collected from 384 Gen Z respondents. Spearman’s correlation analysis showed that performance expectancy has the strongest positive relationship with behavioural intention to use, with correlation coefficient of 0.624, followed by social influence and effort expectancy. In contrast, perceived risk showed negative relationship between behavioural intention to use. These findings highlight the importance of perceived usefulness, ease of use, and social acceptance to encourage intention to use BNPL services, while emphasizing the need to address privacy and financial risk concerns. This study contributes the existing literature on the use of fintech and provides valuable insights for BNPL service providers to enhance user trust, promote responsible use, and support the sustainable growth of the digital payment’s ecosystem in Malaysia.